GREEN MUSTARD PLANT CULTIVATION TECHNIQUE (Brassica Juncea L): TEKNIK BUDIDAYA TANAMAN SAWI HIJAU (Brassica Juncea L) - Imelda Theresia Lehalima; Ayu A. Wendra; Asniati Rumra; La Sudin; Sarah Rumahenga; Dalesi Latuconsina; Rina Rosa Resley; Ainun Mardhiya Ruslin; David Dompeipen; Nur Rizqiah Ibrahim (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2021)
Green mustard plants (Brassica juncea L.) adapt well in hot and cold air places so that they can be cultivated in highland and lowland areas of mustard plants will develop very well. For that, in the Middle-Central Village is very suitable for planting mustard plants because it is located in the lowlands to the highlands. This activity was carried out using observation methods between KKN Students of XLVIII Force of Pattimura University ambon in 2021 in Central-Central Village with several farmers and devices of The Middle-Central Village. located in the backyard of the Village office. The purpose of this activity is to provide an understanding of the cultivation of mustard without the use of chemical fertilizers where the chemicals if used continuously will interfere with human health and pollute the environment.